Calling for a Buddhist Theology of Dementia - Kiblinger, Kristin Beise (Buddhist Christian studies, 2020)
Traditionally, religious discourses and practices have assumed cognitive abilities. This article argues for the need to reexamine our theologies in light of the prevalence of Alzheimer's disease and related dementias that cause severe cognitive impairment. Challenges posed by dementia for theological anthropology, ecclesiology, and soteriology are explored. Explaining responses to dementia found in the Christian theological literature, the essay then asks what a Buddhist version of theology-after-dementia might look like, suggesting in preliminary fashion some potential Buddhist resources. Overall, the piece begins, calls for, and hopes to stimulate Buddhist, and Buddhist-Christian comparative, work in this area.